PERSEPSI IBU PRIMIGRAVIDA TENTANG HUBUNGAN SEKSUAL SELAMA KEHAMILAN TRIMESTER III DI POLI HAMIL RUMAH SAKIT BHAYANGKARA WATUKOSEK - HETY, DYAH SIWI (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2016)
Stop having sex but no medical reason is a mistake, because bagia important than support one another is the way you have sex. In a preliminary study on Poly RS Bhayangkara Watukosek show that 1 out of 10 women are not sexual intercourse during pregnancy until the third trimester because of fear. This can be caused by a lack of information about sex during pregnancy, especially pregnancy. Factors that may affect such physiological changes of pregnancy and psychological factors, such as fear of hurting the fetus or fear due to infection due to rupture.This study used a descriptive research design with accidental sampling technique. The sample of this research is all primigravida who were 40 respondents to the instrument in this study was a questionnaire.From the results of the study on 40 respondents showed that 25 respondents have a positive perception were 15 respondents had a negative perception.The amount of the percentage of positive perception primigravida against sexual intercourse during the third trimester of pregnancy due to the large majority of respondents have sufficient understanding and knowledge about sexual intercourse during pregnancy, thus affecting the perception changes primigravidaKeywords: Perception, pregnancy, sex.